Anionic Redox Activities Boosted by Aluminum Doping in Layered Sodium‐Ion Battery Electrode. Issue 3 (27th January 2022) - Cheng, Chen; Ding, Manling; Yan, Tianran; Jiang, Jinsen; Mao, Jing; Feng, Xuefei; Chan, Ting‐Shan; Li, Ning; Zhang, Liang
Abstract: Sodium‐ion batteries (SIBs) have attracted widespread attention for large‐scale energy storage, but one major drawback, i.e., the limited capacity of cathode materials, impedes their practical applications. Oxygen redox reactions in layered oxide cathodes are proven to contribute additionally high specific capacity, while such cathodes often suffer from irreversible structural transitions, causing serious capacity fading and voltage decay upon cycling, and the formation process of the oxidized oxygen species remains elusive. Herein, a series of Al‐doped P2‐type Na0.6 Ni0.3 Mn0.7 O2 cathode materials for SIBs are reported and the corresponding charge compensation mechanisms are investigated qualitatively and quantitatively. The combined analyses reveal that Al doping boosts the reversible oxygen redox reactions through the reductive coupling reactions between orphaned O 2p states in NaOAl local configurations and Ni 4+ ions, as directly evidenced by X‐ray absorption fine structure results. Additionally, Al doping also induces an increased interlayer spacing and inhibits the unfavorable P2 to O2 phase transition upon desodiation/sodiation, which is common in P2‐type Mn‐based cathode materials, leading to the great improvement in capacity retention and rate capability. This work provides deeper insights into the development of structurally stable and high‐capacity layered cathode materials for SIBs with anion–cation synergetic contributions. Abstract : An appropriate amount of Al doping into the transition metal slabs of Na‐deficient layered Na0.6 Ni0.3 Mn0.7 O2 cathode materials can not only suppress the unfavorable P2–O2 phase transition but also boost the reversible oxygen redox through a reductive coupling mechanism between the isolated O 2p states in the NaOAl configuration and Ni 4+ ions, leading to improved electrochemical performance.